ANSWER
![a=6,\text{ }b=8,\text{ }c=-2](https://img.qammunity.org/2023/formulas/mathematics/college/e4khzgrvfhz6t5iy9x2c2t4qqy1r1k55kt.png)
Step-by-step explanation
We want to rewrite the given quadratic equation in standard form.
The standard form of a quadratic equation is given by:
![ax^2+bx+c=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/mvkhuzwnjhb4epaf7jjcoq2vi4zdi4350m.png)
To rewrite the given equation, collect like terms and simplify:
![\begin{gathered} 8x+7x^2-2=x^2 \\ \\ 8x+7x^2-2-x^2=0 \\ \\ 8x+7x^2-x^2-2=0 \\ \\ 8x+6x^2-2=0 \\ \\ 6x^2+8x-2=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dmv2yoofo1lxd5v9o0a6tc0tt2r1j4tuu6.png)
Comparing the equation to the standard form, we have that:
![a=6,\text{ }b=8,\text{ }c=-2](https://img.qammunity.org/2023/formulas/mathematics/college/e4khzgrvfhz6t5iy9x2c2t4qqy1r1k55kt.png)
That is the answer.